Structural Evaluation of Mechanically Alloyed and Heat-Treated Ti-25at-%Si Powders - de Souza, Marisa Aparecida [UNESP] (2012)
This work discusses on the structural evaluation of mechanically alloyed and heat-treated Ti-25at%Si powders. The milling process was conducted in a planetary ball mill using stainless steel balls/vials, 200 rpm and ball-to-powder weight ratio of 5:1, whereas the heat treatment was conducted under Ar atmosphere at 1100 C for 4 h. Samples were characterized by X-ray diffraction, differential scanning calorimetry, scanning electron microscopy and energy dispersive spectrometry. The Si peaks disappeared after milling for 30h, indicating that the Si atoms were dissolved into the Ti lattice in order to form an extended solid solution. The Ti peaks were broadened and their intensities reduced for longer milling times whereas a halo was formed in Ti-25Si powders milled for 200h suggesting that an amorphous structure was achieved. The crystallite size was decreased with increasing milling times. A large Ti3Si amount was found in mechanically alloyed Ti-25at%Si powders after heating at 1100 degrees C for 4h.